Differential impact of biologically effective dose in distal versus proximal gamma knife targets for trigeminal neuralgia - Hao Deng; Yuan Gao; Yuan Gao; Yang Wu; Mengqi Wang; Linglong Xiao; Runlin Chen; Zhujun Zhang; Wei Pan; Wei Pan; Wei Wang; Wei Wang (Frontiers in Neurology)
We report the results of a long-term follow-up series in our center to verify the impact of biologically effective dose (BED) on the efficacy and safety of Gamma Knife radiosurgery (GKS) in the treatment of primary trigeminal neuralgia (TN). A total of 138 consecutive cases of primary TN receiving GKS were included. A 4-mm collimator was used for all cases, and a median central dose of 85 Gy (range 70–90 Gy) was prescribed. The Barrow Neurological Institute Pain Scale was adopted to evaluate the severity of TN. The median follow-up period was 65.5 months (range 12–147 months). Overall, 123 (89.1%) patients eventually achieved effective relief. The influence of BED on treatment outcomes varied by target location. For patients with distal targets, BED was a significant predictor of treatment failure (OR: 0.996, 95% CI: 0.992–0.999, p = 0.02) and post-GKS complications (OR: 1.002, 95% CI: 1.000–1.004, p = 0.01). However, BED did not significantly influence outcomes in the proximal target subgroup, either for treatment failure or complications. No significant association was found between BED and long-term outcomes in the entire cohort or in any subgroup analysis. Adjusting GKS doses according to BED for the distal target may optimize clinical outcomes in TN patients.